A Plant Oxysterol as a regulator of glucose homeostasis - P. Muthuraman; K. Srikumar (International Journal of Phytomedicine, 2010)
Background: Plant oxysterols like 28-homobrassinolide (HB) exhibit partial structural homology to oxycholesterols. HB’s effect in cell metabolism was therefore investigated using rat model. Results: Oral administration of HB to streptozotocin induced diabetic male albino wistar rats, reduced circulating glucose level to normal level. Serum insulin content was increased by HB treatment. HB elevated the hexokinase (HK) enzyme activity of liver in the experimental animal. Peroxidative damage of cellular lipids was reduced by HB based on quantitative estimates of malonyldialdehyde (MDA) and 4- hydroxy nonenol (4-HNE) content of erythrocyte samples. Conclusion: The antihyperglycemic and antioxidant potential of HB was presented